Building an up-to-date library. Prospero’s Podiani use of booksellers’ catalogues, with special reference to law books - Panzanelli Fratoni, Maria Alessandra (JLIS.it, 2018)
Prospero Podiani (1535 ca. - 1615) is well known as one of the major book-collectors in the 16th century Italy. He was keen to gather the best editions of the most important works published until his own day (along with relevant manuscripts) and to make them available to scholars. In 1582 he agreed with Perugia city governors about the donation of his collection and the foundation of the Biblioteca Augusta. Podiani was able to keep pace with the production of all the major European publishers mainly by acquiring sale catalogues. The evidence for this can be found in the great number of copies of those catalogues (some of which are very rare) that exist today in the Biblioteca Augusta. Along with acquiring printed catalogues, he also produced a series of manuscript lists of books for sale. This article aims to provide an overall presentation of those documents, printed and manuscript, and then to present the results of a more detailed analysis of one of those catalogues where Podiani listed almost exclusively law books printed in the course of the 16th century and to put them in relation to the section of the library dedicated to legal texts.